THE EFFECT OF USING POWERPOINT MEDIA ON STUDENTS’ ENGLISH LEARNING MOTIVATION TO THE ELEVENTH GRADE STUDENTS OF SMK MUHAMADYAH 1 SAMARINDA IN 2018/2019 ACADEMIC YEAR - Godefridus Bali Geroda; Widi Syahtia Pane (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2018)
English education is taught in all levels of education. Therefore, it is believed that there are some differences among teaching adults, teenagers and children. In teaching English to adult learners, the suitable media is needed to attract their attention. One of the media that is suitable to adult learners in teaching English is power point. The purpose of this study was to find out whether there is a significant effect of using power point media on students’ English learning motivation to the eleventh-grade students of SMK MUHAMADYAH 1 Samarinda in 2018/2019 Academic Year. The design of this research was quasi-experimental design because it requires one group of students. There were 60 students as the population and 30 students were taken by the researcher as the sample. The result shows that the mean score of students’ English learning motivation is 73.5. It means that the students’ English learning motivation is high. Then t score 4.894 higher than t tab value 2.042 with the level of significance 0.5%. Based on interpretation, it can be concluded that there is a significant effect of using power point media on students’ English learning motivation to the eleventh-grade students of SMK MUHAMADYAH 1 Samarinda.